The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4236/wjnst.2019.94012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dosimetric Performance and Global Uncertainty of the Harshaw 6600 Plus System Used to Staff Monitoring in Côte d’Ivoire

Abstract: The objective of this work is to check the dosimetric performances of the TLD-100 as stated by the manufacturer as well as the technical standards of radiation protection. The purpose of the performance audit is to assess the inhomogeneity of TLD sensitivity, repeatability and reproducibility, linearity, energy dependence, angular dependence, and fading. All tests were performed under the conditions of ambient temperature and relative humidity recommended by the manufacturer. We began the study by calibrating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Sabar et al, likewise, reported that there could be very high deviation (above 40%) below 0.3mGy (18). This was also supported by Kouakou et al, who evaluated dosimetric performance and uncertainty for TLD-100, and reported that a proportion of TL chips were unable to measure accurately at 0.1-10mGy (19). A study by Kadir et al investigated the uncertainty associated with the energy response of TLD-100 to an ideal dose, which had a maximum deviation of 125.04% for Hp (0.07) against 45.22% for Hp (10) at 24keV, with the shallow dose exhibiting the higher uncertainty (20).…”
Section: Discussionmentioning
confidence: 53%
“…Sabar et al, likewise, reported that there could be very high deviation (above 40%) below 0.3mGy (18). This was also supported by Kouakou et al, who evaluated dosimetric performance and uncertainty for TLD-100, and reported that a proportion of TL chips were unable to measure accurately at 0.1-10mGy (19). A study by Kadir et al investigated the uncertainty associated with the energy response of TLD-100 to an ideal dose, which had a maximum deviation of 125.04% for Hp (0.07) against 45.22% for Hp (10) at 24keV, with the shallow dose exhibiting the higher uncertainty (20).…”
Section: Discussionmentioning
confidence: 53%
“…The Harshaw 6600 Plus system, consisting of a reader and dosimeters whose performance characteristics and overall uncertainty [4] [5] were evaluated before use, allowed the doses received by the operators to be assessed according to their position in the room. For the dosimetric evaluation, each operator was equipped with one or more dosimeters to assess the effective dose and equivalent doses to the extremities and lens of the eye for the radiological procedure performed.…”
Section: Radiological Risk Assessmentmentioning
confidence: 99%